Approach to Pregnancy Affected by Kell Alloimmunization - Serdar Aykut; Suleyman Cansun Demir; Ismaıl Cuneyt Evruke; Mete Sucu; Fatma Islek Uzay; Mesut Avan; Ozge Keles Bayer; Emre Yalcin (Case Reports in Hematology)
Hemolytic disease of the fetus and newborn (HDFN) is the development of anemia, hyperbilirubinemia, and finally hydrops fetalis in the fetus when antibodies to antigens on the surface of erythrocytes are transferred from the placenta to the fetus. The most common cause is D-HDFN. K (KEL1) from the Kell blood group system is the most potent immunogenic antigen after D among all blood group antigens. K-HDFN occurs in 0.1–0.3% of pregnant women. It accounts for 10% of cases of antibody-mediated severe fetal anemia. We present a successful management of Kell alloimmunization in a pregnant woman who had 3 times pregnancy loss with hydrops fetalis due to K-HDFN and who was proven to have K-HDFN in the postnatal period in her last pregnancy.